2013
DOI: 10.1007/s11011-013-9399-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of BDNF polymorphisms on Wilson’s disease susceptibility and clinical course

Abstract: Susceptibility to Wilson’s disease (WD) and its clinical manifestations are thought to be affected by genetic factors, including polymorphisms. The role of brain-derived neurotrophic factor (BDNF) in the pathogenesis of neurodegenerative diseases is now widely discussed. The aim of the present study was to evaluate the frequency of the BDNF Val66Met (G-196A) and C-270T polymorphisms in WD patients and in healthy controls, and to determine the role of these polymorphisms in the clinical characteristics of WD. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…To ensure that the age of onset of WD is not vastly different between individuals carrying ԑ4 allele and those who are not, we checked the age distribution and mean age of both the groups, suggesting that presence of ԑ4 allele is not affecting survival of the patients (mean age, 13.07 ± 5.57 vs. mean age, 12.45 ± 5.53; P‐ value = 0.61). Similar to our finding, other studies on WD reported that variants of DMT1 and BDNF are associated with the disease (Przybylkowski, Gromadzka, & Czlonkowska, ; Mirowska et al., ), although no plausible explanation could be provided behind the association. Expressional variability, incomplete penetrance, environmental influences or epigenetic modifications are common features for a complex disease; however, recent studies imparted knowledge about such complexity to occur even in case of a monogenic disease.…”
Section: Discussionsupporting
confidence: 89%
“…To ensure that the age of onset of WD is not vastly different between individuals carrying ԑ4 allele and those who are not, we checked the age distribution and mean age of both the groups, suggesting that presence of ԑ4 allele is not affecting survival of the patients (mean age, 13.07 ± 5.57 vs. mean age, 12.45 ± 5.53; P‐ value = 0.61). Similar to our finding, other studies on WD reported that variants of DMT1 and BDNF are associated with the disease (Przybylkowski, Gromadzka, & Czlonkowska, ; Mirowska et al., ), although no plausible explanation could be provided behind the association. Expressional variability, incomplete penetrance, environmental influences or epigenetic modifications are common features for a complex disease; however, recent studies imparted knowledge about such complexity to occur even in case of a monogenic disease.…”
Section: Discussionsupporting
confidence: 89%
“…82 Patients with WD more frequently harbored BDNF polymorphisms [Val/Val (−196 G/G) and −270 C/T] than healthy controls and asymptomatic WD patients. 83 However, no association was identified between any BDNF polymorphism and disease presentation (hepatic vs. neurological) or age of onset of WD.…”
Section: Potential Modifier Genesmentioning
confidence: 98%
“…155 Furthermore, certain SNPs in BDNF are more frequent in symptomatic WD patients versus healthy controls and asymptomatic WD patients. 83 In humans, meditation can increase BDNF levels, 156 alters histone modifications, and downregulates proinflammatory genes. 151 …”
Section: Modifiers Of Epigenetic Regulation: Diet Exercise Stresmentioning
confidence: 99%
“…Later on, it was also found in immune cells, such as lymphocytes and monocytes [1,3]. It was stated that the three areas where BDNF is most active are the hippocampus, cortex, and basal forebrain [4,5]. Altered levels of BDNF, both in the circulating blood and in the CNS tissues, have been reported to be involved in the pathogenesis of neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease (PD), amyotrophic lateral sclerosis (ALS), Huntington's disease (HD), and multiple sclerosis (MS) as well as in ischemic stroke [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%